2008
DOI: 10.4067/s0716-078x2008000200002
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in a physiological thermoregulatory mechanism: the case of the lizard Liolaemus tenuis (Liolaeminae)

Abstract: Intraspecific variation in a physiological thermoregulatory mechanism: the case of the lizard Liolaemus tenuis (Liolaeminae) Blindern, N-0316 Oslo, Norway; *e-mail for correspondence: marvidal@udec.cl, marcela.vidal@gmail.com ABSTRACTThe interspecific variation of heating rates in Liolaemus lizards, suggests an adaptive value of this physiological thermoregulatory mechanism, which would allow lizards to cope with the environmental thermal restrictions, imposed to behavioral thermoregulation. This trend has bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Evidence that thermal physiology evolves in response to climate at multiple spatial scales raises the possibility of similar variation at an intra-population level in response to variation in the fine-scale microclimatic conditions individuals occupy. Indeed, most of the evidence that individuals within the same populations can occupy different microclimate space stems, indirectly, from literature investigating sex-specific differences in habitat use or behaviour (Cryan and Wolf, 2003;Lailvaux et al, 2003;Beal et al, 2014;Liwanag et al, 2018;Vidal et al, 2008;Cameron et al, 2018). For example, sex-specific habitat use is prevalent in ectothermic western Indian anoles (Butler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that thermal physiology evolves in response to climate at multiple spatial scales raises the possibility of similar variation at an intra-population level in response to variation in the fine-scale microclimatic conditions individuals occupy. Indeed, most of the evidence that individuals within the same populations can occupy different microclimate space stems, indirectly, from literature investigating sex-specific differences in habitat use or behaviour (Cryan and Wolf, 2003;Lailvaux et al, 2003;Beal et al, 2014;Liwanag et al, 2018;Vidal et al, 2008;Cameron et al, 2018). For example, sex-specific habitat use is prevalent in ectothermic western Indian anoles (Butler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown additional physiological abilities, including decreases in peripheral blood flow and heart rate during cooling that slows heat loss to the environment [ 10 , 15 ], a low hematocrit that offers lower resistance to flow and is less energetically costly to pump [ 9 ], and a muscle in the internal jugular vein [ 1 ] that restricts venous flow to the body from head [ 4 , 5 , 17 ]. To make physiological thermoregulation even more complex, differing inter- and intraspecific thermoregulatory abilities and preferences are found among lizards, and variations in individual behavior can influence thermoregulatory patterns [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies focused on the intrinsic physiological thermoregulatory capabilities in reptiles that allow squamates to “fine tune” or subtly influence temperature control. The earlier works on physiological thermoregulation in squamates focused on the ability to establish a head-to-body temperature differential [ 1 , 4 , 10 , 18 ] indicating that head temperature can be controlled within narrow limits [ 18 , 21 23 ]. Typically, when squamates first exit their refugium, head and body temperatures are roughly equivalent [ 4 , 5 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lizard thermoregulation at high altitudes could be explained by two non-mutually exclusive hypotheses: (1) by behavioral responses to the variation in environmental temperature to compensate the effects of elevation on the thermal environment (Hertz & Huey, 1981;Hertz, 1981Hertz, , 1992Hertz et al, 1993;Smith & Ballinger, 1994;Gvoždík, 2002) and (2) by physiological adaptation to low temperatures at high elevations (Hertz, 1981;Vidal et al, 2008;Ibargüengoytía et al, 2010;Muñoz et al, 2014). Both hypotheses are supported by intraspecific evaluation of T b and T pref in populations at different altitudinal distribution in Anolis (Hertz & Huey, 1981;Hertz, 1981Hertz, ,1992Hertz et al, 1993;Muñoz et al, 2014).…”
Section: Discussionmentioning
confidence: 92%